Psychological Well-Being pada Korban Kekerasan Seksual - Sitohang, Anggelina Veronica; Alfita, Laili (Universitas Medan Area, 2025)
This study aims to look at the psychological well-being of victims of sexual violence at the Belawan Fishing Community Assessment and Development Center which is located in the Land and Sea Coast villages. The sampling technique was a total of 35 people. Data collection was used using a psychological well-being scale. Based on the results of a descriptive analysis of psychological well-being in victims of sexual violence at the Belawan Fishermen Community Assessment and Development Center, the value of the autonomy aspect was 19%, the value of the environmental mastery aspect was 17%, the value of the personal development aspect was 17%, the value of the positive relationship aspect with others was 16%, the value of the life goal aspect was 16%, and the average value of the self-acceptance aspect was 15%. Based on the results of this analysis, it can be known that the one that has the highest percentage, namely the value of the autonomous aspect of 19%, and the one that has the lowest percentage, namely the self-acceptance aspect of 15%, based on the table, it is known that victims of sexual violence at the Center for the Study Development of the Belawan Fishermen Community have low self-acceptance and high autonomy where the victim feels independent and has control over their life